Exploring Smart Renewable Investment in Green Financial Mechanism for Achieving Carbon Neutrality: An Empirical Analysis of the ASEAN Economy - Durohman, Hapid; Khoirunnisa, Annes N. (Indonesian Journal of Energy, 2026)
Smart renewable energy investment is increasingly recognized as a critical component of green financial mechanisms aimed at achieving carbon neutrality, particularly within the ASEAN region, which faces the dual challenge of sustaining economic growth while mitigating environmental degradation. However, the effectiveness of such investments is influenced by complex factors, including geopolitical instability, environmental constraints, and disparities in financial access. Our study empirically examines the dynamic relationship between smart renewable investment, green finance, and carbon emissions in seven ASEAN economies over the period 2001–2023. Employing second-generation panel cointegration techniques, specifically the Continuously Updated Fully Modified and Continuously Updated Bias-Corrected estimators, this analysis accounts for cross-sectional dependence, heterogeneity, and non-stationarity in the panel data. The results reveal that both renewable energy investment and green finance exert a statistically significant negative impact on CO? emissions, confirming their effectiveness in facilitating the region’s transition toward low-carbon development. In contrast, economic indicators such as foreign direct investment, gross domestic product growth, and gross fixed capital formation are positively correlated with emissions, highlighting the environmental costs associated with traditional growth trajectories. Moreover, geopolitical risk is identified as a critical factor exacerbating emissions, suggesting that regional instability can hinder sustainable energy deployment and delay decarbonization efforts. The policy implications of these findings highlight the importance of establishing stable and harmonized green finance frameworks in ASEAN, including fiscal incentives, public–private collaboration, and the integration of geopolitical risk assessments into national energy planning. Furthermore, the development of regional green capital markets and innovative mechanisms such as emissions trading and carbon pricing is deemed crucial to strengthening cross-border investment flows and supporting the transition toward sustainable development.